Functional Characteristics and Lipid Lowering Activity of Auricularia heimuer Soluble Dietary Fiber - Xueyu SHANG; Heriban MEI; Ling SU; Qi WANG (Shipin gongye ke-ji)
In this study, the residue of Auricularia heimuer polysaccharide after hot water extraction was used as raw material, and the soluble dietary fiber (HSDF) of A. heimuer was extracted by compound enzyme method. Its molecular weight, monosaccharide composition and sugar chain composition were analyzed, its water holding capacity, oil holding capacity, swelling power and other physical and chemical properties were detected, and its lipid-lowering activity in vitro was evaluated by measuring cholesterol adsorption capacity, lipase inhibition rate and cholate binding rate. The obese animal model was constructed by high fat diet (HFD) C57BL/6J mice, and treated with A. heimuer soluble dietary fiber. The body weight, biochemical indexes, and pathological changes of liver tissue and adipose tissue of HSDF treated obese mice were evaluated, and its lipid-lowering efficacy in obese mouse model was explored. Results showed that the relative molecular weight of HSDF was 4.14×105 Da, which was a mixture of mannose, glucuronic acid, glucose, galactose, xylose and fucose. The molar ratio was 1808.87:0.00278:4.43:2.13:2.84:5.01. The average water holding capacity of HSDF was (11.62±0.302) g·g−1, the average oil holding capacity was (2.95±0.259) g·g−1, the average swelling capacity was (12.7±0.434) mL·g−1, and the adsorption capacity of intestinal cholesterol was 6.63 mg·g−1. When the concentration was 1.2 mg·mL−1, the binding rate of sodium glycocholate and sodium taurocholate could reach 92.91% and 90.93%. In addition, HSDF with a concentration of 2.0 mg·mL−1 had a 75% inhibition rate of pancreatic lipase, and had good lipid-lowering activity in vitro. At the same time, HSDF could significantly (P<0.05) improve the organ index of HFD mice, improve the lipid accumulation, inflammatory cell infiltration in the liver and adipocyte enlargement in adipose tissue of HFD mice, and improve the cell area of white adipose tissue of epididymis by more than 50%, which had a good lipid-lowering effect in vivo. The results can provide data support and theoretical basis for the subsequent research on dietary fiber of A. heimuer and the research and development of functional food.